ANALISIS MISKONSEPSI PADA MATERI FISIKA DI KOTA PADANGSIDIMPUAN - Elisa, Elisa; Sri Rezeki, Happy; Ginting, Nurmaini; Rusdi, Muhammad; Siregar, Rahmat Fauzi; Masroito, Masroito (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
This study aims to identify subject matter that still experiences misconceptions among students. Interviews were conducted with a number of teachers from several high schools in Padangsidimpuan city, namely SMA Negeri 2, SMA Negeri 6, and SMA Negeri 7 Padangsidimpuan. The sampling technique used was random sampling. This study used a descriptive method, and the data was analyzed descriptively as well. In SMA Negeri 2 Padangsidimpuan, as many as 54.54% of students experienced misconceptions on the material of Newton's Third Law which was classified as a high category. For Thermodynamics material, the level of student misconceptions reached 31.74% with a moderate category. Misconceptions on Quantum Physics material were at 8.48% (low category), while for the Concept of Motion it was 5.24% also with a low category. In SMA Negeri 6 Padangsidimpuan, the percentage of students who experienced misconceptions on Newton's Third Law reached 58.02% (high category). Meanwhile, in Thermodynamics material, it is only 2.72% (low category), Quantum Physics is 7.52% (low category), and Motion Concept is 31.74% (medium category). Meanwhile, in SMA Negeri 7 Padangsidimpuan, students who experience misconceptions in Newton's Third Law are 50.63% (high category). For Thermodynamics material, the percentage is 31.74% (medium category), Quantum Physics is 8.48% (low category), and Motion Concept is 5.24% (low category).